Disc wall structural abnormalities can act as initiation sites for herniation - K Wade (European Cells & Materials, 2020)
Both posture and loading rate are key factors in the herniation process and can determine the failure mechanism of the disc. The influence of disc structure on the herniation process has yet to be directly observed, thus the aim of this study was to test the hypothesis that discs containing greater levels of pre-existing disruption would be more vulnerable to herniation when subjected to severe levels of posture and loading. 30 ovine lumbar motion segments were subjected to combinations of 4 loading conditions (0 - 12° flexion,0 - 9° lateral bending, 0 - 4° axial rotation, 0-1500 N axial compression) for 1000 loading cycles at 2 Hz in a dynamic disc loading simulator. The discs were scanned in an ultra-high field MRI (magnetic resonance imaging, 11.7 T) prior to and following testing. 4 discs herniated and 7 discs suffered nucleus displacement. These discs contained pre-existing defects in the central dorsal annulus. Generally, following testing, discs contained more dorsal annulus disruption, including 7 discs which developed similar characteristic defects although these did not herniate. Overall, more severe complex postures produced more disruption. While more severe postures such as twisting and bending increased disc damage, these results are probably the first directly showing that naturally occurring defects in the disc can act as initiation sites for herniation. The clinical significance of these findings is that, in principle at least, MRI based techniques could be capable of identifying vulnerable discs, with the obvious caveat that further correlation with clinical techniques is required.